Where do we go from here? Market access and regional development in Italy (1871 - 1911) - Anna Missiaia (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2015)
Italy has been characterized, throughout its history as a unified country, by large regional differentials in the levels of income, industrialization and socio-economic development. This paper aims at testing the New Economic Geography hypothesis on the role of market access in explaining these regional differentials. We first quantify market access of the Italian regions for benchmark years from 1871 to 1911 following Harris (1954). We then use these estimates to study the causal link between GDP per capita and market potential following Head and Mayer (2011). The main result of this paper is that only domestic market potential, which represents the home market, shows a "traditional" North-South divide. When international markets are introduced, the South does not appear to lag behind. Regression analysis confirms that market potential is a strong determinant of GDP per capita only in its domestic formulation. This suggests that the home market in this period mattered far more for growth than the international markets, casting new light on one of the classical explanations to the North-South divide.
Keywords: N33; N73; N93; O18; R11; 330; Economic Geography; Economic History of Italy; Market Potential